Healthy urban planning: an institutional policy analysis of strategic planning in Sydney, Australia. (23rd June 2019) - Harris, Patrick; Kent, Jennifer; Sainsbury, Peter; Riley, Emily; Sharma, Nila; Harris, Elizabeth
Abstract: Rapid urbanization requires health promotion practitioners to understand and engage with strategic city planning. This policy analysis research investigated how and why health was taken up into strategic land use planning in Sydney, Australia, between 2013 and 2018. This qualitative study develops two case studies of consecutive instances of strategic planning in Sydney. Data collection was done via in-depth stakeholder interviews ( n = 11) and documentary analysis. Data collection and analysis revolved around core categories underpinning policy institutions (actors, structures, ideas, governance and power) to develop an explanatory narrative of the progress of 'health' in policy discourse over the study period. The two strategic planning efforts shifted in policy discourse. In the earlier plan, 'healthy built environments' was positioned as a strategic direction, but without a mandate for action the emphasis was lost in an economic growth agenda. The second effort shifted that agenda to ecological sustainability, a core aspect of which was 'Liveability', having greater potential for health promotion. However, 'health' remained underdeveloped as a core driver for city planning remaining without an institutional mandate. Instead, infrastructure coordination was the defining strategic city problem and this paradigm defaulted to emphasizing 'health precincts' rather than positioning health as core for the city. This research demonstrates the utility in institutional analysis to understanding positioning health promotion in city planning. Despite potential shifts in policy discourse and a more sophisticated approach to planning holistically, the challenge remains of embedding health within the institutional mandates driving city planning.